2019
DOI: 10.1080/02739615.2019.1666009
|View full text |Cite
|
Sign up to set email alerts
|

Child and adolescent suicide: contributing risk factors and new evidence-based interventions

Abstract: Our goal of this special issue is to detail and describe the current epidemiology of suicide among children and adolescents, as well as highlight important risk factors and evidence-based treatment options. To accomplish this, our issue is organized in two major sections: (1) contributing factors to the emergence of child and adolescent suicide, and (2) evidence-based treatment of child and adolescent suicide. Within the issue, authors discuss risk factors of anxiety, sleep problems, child sexual abuse, and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…34 The increased risk for suicide associated with anxiety disorders, depressive disorders, and substance abuse is well known. 35,36 Because many individuals do not respond optimally to first-line treatments, which often include psychiatric medications, 37 children at end of life should be assessed and managed by a psychiatric specialty provider with expertise in selecting from available treatment options. We urge hospice and palliative care nurses to familiarize themselves with local psychiatric treatment resources and colleagues, to facilitate the process of psychiatric referral or ideally, to add a psychiatric clinician as a permanent part of the pediatric hospice and palliative care team.…”
Section: Discussionmentioning
confidence: 99%
“…34 The increased risk for suicide associated with anxiety disorders, depressive disorders, and substance abuse is well known. 35,36 Because many individuals do not respond optimally to first-line treatments, which often include psychiatric medications, 37 children at end of life should be assessed and managed by a psychiatric specialty provider with expertise in selecting from available treatment options. We urge hospice and palliative care nurses to familiarize themselves with local psychiatric treatment resources and colleagues, to facilitate the process of psychiatric referral or ideally, to add a psychiatric clinician as a permanent part of the pediatric hospice and palliative care team.…”
Section: Discussionmentioning
confidence: 99%
“…This study reported that early therapeutic contact and completing a safety plan may be warranted for CYP (Brent et al, 2009). More recently safety planning for CYP has been identified as a promising new approach (Rufino & Patriquin, 2019), but more research is required about this specific intervention and its impact on CYP (Drapeau, 2019). There is also a particular need for a systematic scoping review of the effectiveness of safety planning for CYP to better identify the complexities and/or challenges involved in the use of this intervention.…”
Section: Introductionmentioning
confidence: 97%
“…12 Specifically, in children and adolescents, general anxiety disorder was shown to be a risk factor for suicidal behavior. 13 In addition, people with anxiety disorders frequently have more difficulty regulating their emotions than those without such disorders. 14,15 Emotions promote behavioral responses, guide thinking in different situations, aid decision-making, facilitate motor responses, and govern interpersonal interactions, making them a prominent factor in psychological research.…”
mentioning
confidence: 99%
“…A study of over 7000 adults from The Netherlands showed that anxiety disorders were very common among those who reported suicidal behavior and that, after adjusting for comorbid mental health disorders, anxiety disorders were a risk factor for suicidal ideation and suicide attempts 12. Specifically, in children and adolescents, general anxiety disorder was shown to be a risk factor for suicidal behavior 13. In addition, people with anxiety disorders frequently have more difficulty regulating their emotions than those without such disorders 14,15…”
mentioning
confidence: 99%